Reconstitution of ST2 (IL-1R4) specific for IL-33 activity; no suppression by IL-1Ra though a common chain IL-1R3 (IL-1RAcP) shared with IL-1. (July 2016) - Jo, Seunghyun; Kim, Eunsom; Kwak, Areum; Lee, Jungmin; Hong, Jaewoo; Lee, Jongho; Youn, Sulah; Bae, Suyoung; Kim, Busun; Ryoo, Soyoon; Kang, Tae-Bong; Her, Erk; et al.
Highlights: Molecular reconstitution of functional ST2 in human lung epithelial A549 cells. HMC-1 cells respond to IL-33, but do not respond to IL-1β. A549/ST2 cells responding to mature IL-33, but unresponding to precursor IL-33. IL-1Ra inhibited IL-1α/β activity, but failed to block IL-33 activity in A549/ST2 cells. ST2 (IL-1R4) is necessary but not sufficient for IL-33 activity. Abstract: Interleukin-33 (IL-33) receptors are composed of ST2 (also known as IL-1R4), a ligand binding chain, and IL-1 receptor accessory protein (IL-1RAcP, also known as IL-1R3), a signal transducing chain. IL-1R3 is a common receptor for IL-1α, and IL-1β, IL-33, and three IL-36 isoforms. A549 human lung epithelial cells are highly sensitive to IL-1α and IL-1β but not respond to IL-33. The lack of responsiveness to IL-33 is due to ST2 expression. ST2 was stably transfected into A549 cells to reconstitute its activity. RT-PCR and FACS analysis confirmed ST2 expression on the cell surface of A549/ST2 cells. Upon IL-33 stimulation, A549/ST2 cells induced IL-8 and IL-6 production in a dose dependent manner while A549/mock cells remained unresponsive. There was no difference in IL-1α and IL-1β activity in A549/ST2 cells compared to A549/mock cells despite the fact that IL-33 shares IL-1R3 with IL-1α/β. IL-33 activated inflammatory signaling molecules in a time- and dose-dependent manner. Anti-ST2 antibody and soluble recombinant ST2-Fc abolished IL-33-induced IL-6 and IL-8 production in A549/ST2 cells but the IL-1 receptor antagonist failed to block IL-33-induced cytokines. This result demonstrates for the first time the reconstitution of ST2 in A549 human lung epithelial cell line and verified its function in IL-33-mediated cytokine production and signal transduction.